The Profit and Berkah (Blessing) from Palm SAP Production to Gain Optimal Mashlahah in Rokan Hulu-Riau Province - Rosyetti, Rosyetti; Ghafar Ismail, Abdul; Naula Oktaviani, Rona (IKONOMIKA, 2021)
Palm sap is produced from male flower bunches that are cut off and tapped. Palm sap tapped by palm farmers is valuable since it generates profit and blessing for farmers. This study aims to determine and analyze the production of palm sap by sugar palm farmers in Rokan Hulu Regency, Riau Province, which has reached the Optimal Mashlahah. The execution of mashlahah in production activities is laba and blessing. Thus, palm sap producers will be capable of determining the combination of laba and berkah in realizing optimal mashlahah. The non-technical content of blessings is found in resources (inputs), results (outputs), and the production process. The data analysis method used was a quantitative method with descriptive data analysis. The model used was the "Comparative Model Approach" with two forms of production stages, namely the production stage containing 95 percent of sharia elements (optimal mashlahah) and the production stage containing < 95 percent of sharia elements (not optimal mashlahah). The data analysis technique in this research is the descriptive technique. The analysis of the production stages used quantitative analysis by examining aspects of resources (inputs), production processes, and results (outputs). These three aspects were analyzed based on physical attributes such as ownership of sugar palm plants and the beneficial value for palm sap producers.Based on the results of the study, it was found that the production of Palm sap in Rokan Hulu Regency, Riau Province had not yet reached the Optimal Mashlahah. This conclusion goes in line with the comparative approach, in which it is stated that the stages of palm sap production based on sharia standards was still far lesser than 95 percent, namely (100 - 46.67) = 53.33 percent. The results of this research provide contribution through recommendation and knowledge for palm sap farmers to apply sharia-based production activity as taught in the Qur'an. This study also instills and grows Islamic values through Qur’an recital groups.Keywords: Profit, Optimal Mashlahah Optimal, Palm Sap